Cropping Systems and Land Use in Sylhet Region (Bangladesh Rice Journal, 2018)
Towards the sustainable food security for a particular area, the policymakers, researchers, extension and development agents need the detailed information of cropping patterns, cropping intensity and crop diversity. Sylhet, a potential region of enormous potentiality of growing crops across the haor area lying below the northeastern Himalyan foothills experience the highest rainfall in the world to make the basin prone to flashflood. That is why, a study was conducted in the region considering all the upazillas during 2016 using the pretested semi-structured questionnaire and validated by appropriate informants with a view to documenting the existing cropping patterns, cropping intensity and crop diversity in the region. As per the study the region is dominated by the rice based cropping pattern. The non-rice based cropping pattern are either few or the area under those cropping patterns are not enough to satisfy the non-rice food requirement of people of the region. Beside these, the cropping patterns and crop diversity appeared as below the expected level. Therefore, much thrust is needed to initiate research and development activities to diversify the single or double-cropped cropping pattern with the introduction of appropriate crops and crop varieties even other non-crop agricultural commodities.Bangladesh Rice j. 2017, 21(2): 273-288